ChemInform Abstract: Ba3(Cr0.97(1)Te0.03 (1))2TeO9: In Search of Jahn—Teller Distorted Cr(II) Oxide. Issue 51 (5th December 2016) - Li, Man‐Rong; Deng, Zheng; Lapidus, Saul H.; Stephens, Peter W.; Segre, Carlo U.; Croft, Mark; Paria Sena, Robert; Hadermann, Joke; Walker, David; Greenblatt, Martha
Abstract: The 6H‐type hexagonal perovskite Ba3 (Cr0.97 Te0.03 )2 TeO9 is prepared by hot press sintering of a mixture of Ba2 TeO5, Cr, and Cr2 O3 (Ba:Cr:Te = 2:1:1; multianvil press, 6 GPa, 1773 K, 4 h; quenching to 25 °C and pressure release over 8—12 h).